New Therapies in the Biological Treatment of Psoriasis: A Review - Mateusz Kamil Ożóg; Alicja Derkacz; Dawid Klimczak; Sara Winkler; Laura Wojciuch (Allergies, 2025)
Psoriasis is a chronic inflammatory autoimmune disease primarily affecting the skin and, in some cases, the joints, and is characterized by erythematous, scaling lesions. Building up the doses has been conventional, but many patients will not obtain good results and a new, more targeted therapeutic strategy is desired. In the past few years, immune checkpoint inhibitors have revolutionized moderate to severe psoriasis management by blocking crucial pro-inflammatory cytokines, introducing new avenues for biological therapies. This review summarizes recent developments in biological therapies, including their mechanisms of action and clinical efficacy. While bimekizumab, an IL-17A and IL-17F inhibitor, strongly suppresses inflammation, selective inhibition of the IL-12/23 pathways is targeted with the small molecule TYK2 inhibitor deucravacitinib. For example, spesolimab, an inhibitor of IL-36 signaling, is being investigated for generalized pustular psoriasis. In this respect, new therapies provide better efficacy and quality of life, target specific psoriasis subtypes, and are safer and more effective than anti-inflammatory treatments. Such therapies could radically inform the standards of care, and the long-term safety and patient-centered outcomes of these innovative strategies will be the subject of continued research.